(untitled) (Research, Society and Development, 2023)
The use of ECMO may help sustain extracorporeal life support in cases where regular less-invasive modalities failed to adequately assist the body in maintaining basic life mechanisms. Typically, VV-ECMO is used in life-threatening respiratory failure. However, experts must consider relative contraindications, answering the question: ‘Will the patient really benefit from this treatment, or will it only add emotional and economic burden, also exposing the patient to various risks of complications?’. The physiology of oxygenation within the lungs, tissues, and ECMO machine, is a modification of the basic principles of respiratory physiology. In typical VV-ECMO cannula insertion, drainage cannula is inserted via the right femoral vein percutaneously and is guided upwards through inferior vena cava with its tip 10 cm below cavoatrial junction while the reinjection cannula will be inserted through the intrajugular vein. This places the artificial lungs in series with the normal lungs rather than in a parallel form. The artificially-oxygenated blood was then returned and mixed with the native venous blood. It is important to measure maximum drainage flow to prevent shunting of the veins by setting the ECMO to the highest flow. Frequent complications include co-infection up to sepsis and coagulopathy up to complications following it. Therefore, it is always beneficial to acquire multidisciplinary judgement, particularly with hematologists, intensivists, and infectious disease specialists prior, during, and post-ECMO use.